Delivery Performance Improvement Using Six Sigma Method: A Case Study at FMC Agricultural Manufacturing - Satyana Primandaru; Soeparno (Jurnal Sosial Humaniora, 2025)
PT. FMC is a manufacturing company to produce pesticides in 3 classifications: herbicides, fungicides and insecticides. The use of pesticides is very important to maintain the quality of the crop. Delivery is an important metric because delivery has big influence to customer satisfaction. The delivery of products may not be late because it will disrupt the consumer production chain. However, PT. FMC delivery performance faces a big issue. This research focuses on how companies are able to identify problems, analyze and solve these problems using the Six Sigma methodology. This method is used because the Six Sigma methodology has a cycle of how companies solve a problem that can disrupt business processes. The research found that problems in the business process are categorized into 3 causes, namely (1) delays in the arrival of material both raw material and packaging material; (2) the customer delays delivery several times; and (3) the Warehouse Leader is late in inputting data and Post Goods Issue.